Public Perceptions of Eigenrichting's Actions in the Khalwat Case - Syaibatul Hamdi; Jalaluddin Jalaluddin; Rizki Syahputra; M. Rezki Andhika (Al Mabhats : Jurnal Penelitian Sosial Agama, 2025)
The phenomenon of "eigenrichting," which refers to actions taken by individuals or groups outside of legal cedures to punish those perceived as criminals, is a significant concern in many societies. Normatively, eigenrichting is not justified and is against the law, as stipulated in Article 170 of the Indonesian Criminal Code concerning violence. This study aims to explore the factors leading to eigenrichting actions, particularly in cases of khalwat (close proximity between members of the opposite sex who are not married) in West Aceh. Employing a qualitative research methodology, specifically empirical legal research, this study examines both legal provisions and their application within the community. The results reveal that eigenrichting actions in West Aceh are primarily driven by five factors: (1) public distrust in law enforcement, (2) insufficient religious knowledge, (3) lack of legal understanding, (4) emotional responses, and (5) spontaneous community reactions. These factors contribute to varied public perceptions of eigenrichting actions against khalwat perpetrators. The study suggests that the community should be encouraged to report such incidents to authorities to prevent extrajudicial actions.